Calcium silicate electromagnetic shielding powder, calcium silicate electromagnetic shielding composite paper and preparation method and application thereof
Patent Information
- Application Number
- CN202611090089.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-09-29
AI Technical Summary
然而,电磁波的无差别辐射也带来了两大核心问题:一是对人体健康的潜在危害,长期暴露于高频电磁波环境中可能引发神经系统紊乱、细胞损伤等病症;二是电子设备之间的电磁干扰(EMI),严重降低精密仪器的测量精度与工作稳定性
1)通过化学镀镍技术对硅酸钙粉体进行功能化改性,镍颗粒不仅附着在多孔硅酸钙表面,还进入了多孔硅酸钙内部,并在硅酸钙表面均匀镀覆了一层镍壳层,成功制备出一种电磁屏蔽粉体,与原始硅酸钙填料相比,不仅显著提升了硅酸钙的附加值,还赋予其导电、导磁和电磁屏蔽功能,不易发生老化,性能稳定,使用寿命长,成本低,有效拓展了硅酸钙在功能材料领域的应用场景。
Smart Images

Figure CN122833890A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the intersection of electromagnetic shielding materials and papermaking technology, and particularly to a calcium silicate electromagnetic shielding powder, a calcium silicate electromagnetic shielding composite paper, its preparation method, and its application. Background Technology
[0002] With the widespread adoption of electronic devices and the rapid development of 5G communication systems, electromagnetic waves are increasingly used in information transmission, intelligent control, and other fields. However, the indiscriminate radiation of electromagnetic waves has also brought two major problems: first, the potential harm to human health, as long-term exposure to high-frequency electromagnetic waves may cause nervous system disorders, cell damage, and other illnesses; second, electromagnetic interference (EMI) between electronic devices, which seriously reduces the measurement accuracy and operational stability of precision instruments. Electromagnetic pollution has become a new source of environmental pollution, following air pollution, water pollution, and noise pollution. Using electromagnetic shielding materials can effectively prevent the harmful effects of electromagnetic interference and radiation.
[0003] Composite particles with a core-shell structure, prepared by chemical plating, possess the superior properties of both the shell metal and the core matrix material, finding wide application in optoelectronic materials, functional fillers, and magnetic materials. Currently, commonly used matrix materials are primarily non-metallic powders, such as polystyrene microspheres, hollow glass microspheres, glass fibers, and carbon fibers. However, traditional electromagnetic shielding substrates, such as polystyrene (PS), polypropylene (PP), and polyurethane (PU), suffer from drawbacks as flexible electromagnetic shielding substrates, including poor thermal stability, non-biodegradability, and limited shielding effectiveness, making them unsuitable for the green and high-performance demands of modern electronics. While metal-based shielding materials offer excellent shielding effectiveness, their high density and susceptibility to corrosion do not align with the lightweight development trends in aerospace and portable electronic devices. Furthermore, existing electromagnetic shielding materials suffer from high cost and complex preparation methods. Therefore, developing novel, green, lightweight, high-shielding-effective, and cost-effective electromagnetic shielding materials has become a research hotspot in the interdisciplinary field of materials science and papermaking engineering.
[0004] Inorganic non-metallic materials possess many advantages, such as wide variety, abundant sources, high performance, and low cost; however, their insulation and wave transmission limitations restrict their applications. Therefore, coating inorganic non-metallic materials with a metallic shell to form a so-called core-shell structure is of significant value in the field of electromagnetic shielding. Compared to metal platings such as gold, silver, and copper, nickel plating not only possesses electrical conductivity but also magnetic permeability, which can increase magnetic loss in the electromagnetic shielding effect, thereby effectively improving the electromagnetic shielding performance of composite materials.
[0005] Existing core-shell structured nickel-plated materials include nickel-plated graphene, nickel-plated carbon fiber, and nickel-plated carbon nanotubes. However, current technologies primarily involve nickel plating on materials that already possess conductivity and electromagnetic shielding effectiveness, thereby further enhancing their electromagnetic shielding performance. There are few examples of nickel plating on materials that are inherently insulating and lack electromagnetic shielding properties. Fly ash-based calcium silicate (FACS), as a novel synthetic paper filler, exhibits significant advantages in improving paper bulk and promoting paper lightweighting. However, FACS has high resistivity, is inherently insulating and non-conductive, and does not intrinsically possess electromagnetic shielding capabilities. Reports on its use in preparing electromagnetic shielding materials are scarce. How to transform it into an electromagnetic shielding material and provide practical applications is one of the new directions for research in this field. Summary of the Invention
[0006] The purpose of this invention is to provide a calcium silicate electromagnetic shielding powder and its preparation method. A uniform nickel shell layer is deposited on the surface of the calcium silicate powder using chemical plating, giving it a certain electromagnetic shielding function, and then it is applied to electromagnetic shielding materials. Based on this, the aforementioned calcium silicate electromagnetic shielding powder is added to paper, thereby providing a calcium silicate electromagnetic shielding composite paper and its preparation method.
[0007] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing calcium silicate electromagnetic shielding powder, comprising: S1: Using calcium silicate powder as raw material, acid etching is performed on it with hydrochloric acid solution, and then the solid is filtered out. S2: After sensitizing the calcium silicate obtained by acid etching in S1 with SnCl2 solution, the solid was filtered off. S3: The sensitized calcium silicate obtained in S2 is placed in an activation solution for activation treatment, washed, then placed in a reducing agent solution for reduction treatment, washed, and filtered to obtain the solid. S4: The calcium silicate obtained in S3 is placed in a chemical plating solution for chemical nickel plating to obtain a nickel-plated calcium silicate suspension. After filtration, washing, and drying, calcium silicate electromagnetic shielding powder is obtained.
[0008] This invention involves a series of pretreatments on calcium silicate powder, including acid etching, sensitization, activation, and reduction. Then, using electroless plating, nickel metal ions are chemically reduced onto the catalytically active calcium silicate surface, forming a metal coating without the passage of external current. This produces a nickel-containing calcium silicate electromagnetic shielding powder, improving the conductivity, magnetism, and electromagnetic shielding properties of calcium silicate. The resulting powder also fully utilizes absorption loss, interface polarization loss, reflection loss, and multiple reflections of electromagnetic waves, generating a synergistic effect of various electromagnetic energy dissipation methods, thereby enhancing the electromagnetic shielding effect. This preparation method also expands the range of substrates that can be selected for electroless plating, allowing calcium silicate to also be used as a substrate material. The operation is simple and easy, the substrate material cost is low, it is easy to mass-produce, and it is suitable for widespread application.
[0009] Further configured, in S1, the calcium silicate powder is porous and honeycomb-shaped, with an average particle size of 11-13 μm. The porous internal structure and wrinkled surface of the calcium silicate powder facilitate the provision of abundant active sites for the attachment of metallic nickel. Nickel particles can be loaded on the surface and in the pores of the porous calcium silicate, enhancing the electromagnetic shielding effect of the product.
[0010] Preferably, the calcium silicate powder is fly ash-based calcium silicate. Fly ash-based calcium silicate (FACS), as a solid waste-based functional filler, has the advantages of being lightweight, having a high specific surface area, and a porous structure. It can not only effectively reduce the overall density of electromagnetic shielding materials, but its abundant channels and surface active sites can also provide an ideal carrier for the loading of metal particles.
[0011] Further, in S1, the acid etching conditions are as follows: temperature 30-60℃, solid-liquid ratio 1g:(50-100)mL, time 10-60min, and the concentration of the hydrochloric acid solution used is 0.3-0.6mol / L. The acid etching treatment roughens the surface of the calcium silicate powder particles, further increasing the specific surface area to improve the adsorption of Sn during subsequent sensitization. 2+ The ability to react with the active catalytic center and the bonding strength between the particles during the activation process also helps to improve the bonding force between the coating and the substrate.
[0012] Further, in S2, the sensitization conditions are as follows: temperature 30-60℃, solid-liquid ratio 1g:(50-100)mL, time 10-60min, and the concentration of the SnCl2 solution used is 10-15g / L. The Sn in the SnCl2 solution... 2+ It has strong reducing properties and can be adsorbed on the surface of non-conductive substrates to form a uniform tin ion film. This film provides a reaction basis for subsequent activation steps, allowing silver particles to act as catalytic centers to trigger reduction reactions in subsequent chemical plating solutions (such as hypophosphite reduction of nickel ions), so that the metal layer is uniformly deposited on the non-conductive substrate.
[0013] Further configured, in S3, the activating solution is a silver nitrate solution with a concentration of 10-13 g / L; the reducing agent is a sodium borohydride solution with a concentration of 40-50 g / L. After silver nitrate is adsorbed onto the substrate surface, sodium borohydride, utilizing its extremely strong reducing properties, directly reduces it to metallic silver (Ag). 0 The generated silver nanoparticles have extremely high specific surface area and catalytic activity, and are deposited on the substrate surface to form activation centers, which rapidly trigger subsequent chemical plating reactions (such as chemical nickel plating).
[0014] Further, in S3, the activation conditions are as follows: temperature 30-60℃, solid-liquid ratio 1g:(50-100)mL, time 10-40min; the reduction conditions are as follows: temperature 30-60℃, solid-liquid ratio 1g:(50-100)mL, time 10-30min.
[0015] Further configured, in S4, the chemical plating solution comprises: 33-36 g / L of C6H5Na3O7·2H2O, 25-30 g / L of NiSO4·6H2O, 15-18 g / L of NaH2PO2·H2O, 3-5 g / L of DMAB, 0.01-0.02 g / L of SDS, and water, with a pH of 10. Chemical plating occurs in the liquid phase, ensuring the coating completely coats the substrate, resulting in high-quality, dense, uniform, and highly conductive coatings. The components of the plating solution are all widely used commercial reagents, readily available, low-cost, and easily scalable for industrial-scale production.
[0016] Further, in S4, the conditions for electroless nickel plating are as follows: temperature 82-87℃, solid-liquid ratio 1g:(50-100)mL, and time 110-150min. When magnetic metal Ni is coated on the surface of FACS, core-shell structured FACS-Ni functional particles can be constructed, endowing them with magnetic loss capability; at the same time, the numerous heterogeneous interfaces (calcium silicate / metallic Ni, metallic Ni / air) on the surface of FACS-Ni particles can cause multiple scattering and reflection of incident electromagnetic waves, prolonging their propagation path inside the material, and thus achieving excellent electromagnetic shielding performance through the synergistic effect of magnetic loss and dielectric loss.
[0017] Secondly, this invention provides a calcium silicate electromagnetic shielding powder, prepared by the aforementioned method for preparing calcium silicate electromagnetic shielding powder, wherein the saturation magnetization of the calcium silicate electromagnetic shielding powder is not less than 15 emu / g. This powder has a porous calcium silicate core layer and a continuous, dense nickel layer as its shell. Nickel particles may also be dispersed within the material. This composite core-shell structure not only enables multiple reflections and absorptions of electromagnetic waves but also generates interfacial polarization losses, giving the insulating material calcium silicate electromagnetic shielding functionality. Furthermore, the electromagnetic shielding effectiveness is greatly improved, with stable performance, long service life, and low cost. It can be used as a filler in the electromagnetic shielding field or prepared independently, greatly expanding the application areas of chemical plating technology.
[0018] Thirdly, the present invention provides an application of calcium silicate electromagnetic shielding powder in electromagnetic shielding materials, wherein the calcium silicate electromagnetic shielding powder is prepared by the aforementioned method for preparing calcium silicate electromagnetic shielding powder.
[0019] Further configurations include using calcium silicate electromagnetic shielding powder as a conductive filler in conductive adhesives, or as a papermaking filler in electromagnetic shielding paper.
[0020] The surface metallization of this calcium silicate electromagnetic shielding powder, with its uniformly distributed and densely crystallized nickel plating, makes the powder less susceptible to external temperature and humidity fluctuations during use, less prone to aging, and consequently exhibits smaller resistivity changes. This results in more stable performance and a longer service life. When used in electromagnetic shielding materials, it enhances the electromagnetic shielding effect and conductivity, while also reducing the production cost of electromagnetic shielding materials.
[0021] Fourthly, the present invention provides a method for preparing calcium silicate electromagnetic shielding composite paper, comprising: S1: Weigh plant fiber and carbon fiber according to the absolute dry mass ratio, mix them, and then loosen and fully disperse them. Then add the aforementioned calcium silicate electromagnetic shielding powder and disperse it evenly to prepare a composite suspension with a total solid content of 0.3-0.7%. S2: The above-mentioned composite suspension is fed into a molding machine and shaped by vacuum-assisted filtration. After pressing and drying, a product with a quantitative content of 60-120 g / m³ is obtained. 2 Calcium silicate electromagnetic shielding composite paper.
[0022] This invention introduces calcium silicate electromagnetic shielding powder into composite paper, which is a typical "multi-component synergistic" material design. Plant fibers determine the basic shape and toughness of the paper, carbon fibers construct a conductive network to achieve efficient electromagnetic shielding, and calcium silicate electromagnetic shielding powder not only assists in absorbing electromagnetic waves through its porous structure, but also significantly improves the material's high temperature resistance, flame retardancy, and structural stability. The three work synergistically to finally prepare a multifunctional electromagnetic shielding composite paper with high shielding effectiveness, excellent mechanical properties, and environmental adaptability, overcoming the physical or functional limitations of single materials.
[0023] Further configured, in S1, the plant fiber is a mixture of sulfate-bleached softwood pulp and hardwood pulp, with a freeness of 40-50°SR. The softwood pulp comprises 70-90% by mass, and the hardwood pulp comprises 10-30% by mass. The plant fiber can uniformly disperse and support inorganic fillers such as carbon fibers and calcium silicate powder, preventing excessive loss or agglomeration of functional powders during papermaking. It also possesses excellent weaving ability, providing basic tensile strength and flexibility to the composite paper through hydrogen bonding between fibers, giving it the basic shape and processing properties of paper. Softwood pulp provides and maintains strength to ensure the long fibers form continuous conductive pathways, while hardwood pulp assists in adjusting smoothness, allowing the composite paper to balance flexibility, strength, and shielding performance.
[0024] Further configuration: In S1, the length of the carbon fiber is 5-8 mm; the carbon fiber mass accounts for 15-18% of the paper's basis weight. Carbon fibers possess excellent electrical conductivity, overlapping within the paper sheet to form a three-dimensional conductive network, strongly reflecting and absorbing electromagnetic waves. This also significantly improves the tensile index and mechanical strength of the composite paper. Compared to traditional metal foil shielding materials, carbon fibers have lower density and better corrosion resistance, aligning with the modern trend towards lightweight and long-life materials.
[0025] Further configured, in S1, the amount of calcium silicate electromagnetic shielding powder added is 20-60% of the paper's basis weight. When electromagnetic waves enter the interior of the composite paper, multiple scattering and reflections occur at the interface between the calcium silicate electromagnetic shielding powder and the fibers, thereby converting electromagnetic energy into heat energy and dissipating it, increasing absorption loss, and further enhancing shielding effectiveness. Simultaneously, it acts as a paper filler, improving the paper's bulk, air permeability, thermal stability, and flame retardant properties, and also enabling the composite paper to maintain stable mechanical properties and shielding effectiveness under harsh environments such as acid, alkali, or high temperatures. The amount of calcium silicate electromagnetic shielding powder added should not be excessive to avoid hindering and damaging the hydrogen bonding between fibers, affecting the pulp's drainage performance, and causing significant reductions in the paper's tensile strength, folding endurance, tear strength, and internal bond strength.
[0026] Further, in S2, the vacuum-assisted filtration molding conditions are: using a 300-1000 mesh screen, a negative pressure of 0.01-0.10 MPa, and a filtration time of 1-10 minutes. During filtration, plant fibers, carbon fibers, and calcium silicate electromagnetic shielding powder overlap and fill each other, achieving rapid dehydration of the composite suspension, fiber interweaving, and paper peeling and transfer. This not only strengthens fiber interweaving and compaction, improving the uniformity of the transverse basis weight distribution of the paper, but also increases the dryness of the wet paper to a level suitable for subsequent pressing, thereby significantly improving the overall dehydration efficiency.
[0027] Further settings include, in S2, the pressing conditions are: pressure of 0.4-0.6 MPa, time of 4-10 min; the drying conditions are: temperature of 105-120℃, time of 5-15 min.
[0028] Fifthly, this invention provides a calcium silicate electromagnetic shielding composite paper, prepared by the aforementioned method for preparing calcium silicate electromagnetic shielding composite paper. This electromagnetic shielding composite paper is a flexible material, characterized by easy processing, a wide shielding frequency band, and good wave absorption performance. It also possesses high strength, high toughness, and high shielding effectiveness, and exhibits long-term stable electromagnetic shielding performance and structural integrity even in extreme environments. It can be used as a material to prevent electromagnetic wave pollution, demonstrating excellent electromagnetic shielding performance, mechanical properties, and environmental adaptability.
[0029] In addition to the aforementioned advantages, the calcium silicate electromagnetic shielding powder, calcium silicate electromagnetic shielding composite paper, their preparation method, and applications provided by this invention also have at least the following beneficial effects: 1) By using chemical nickel plating technology to functionalize calcium silicate powder, nickel particles not only adhere to the surface of porous calcium silicate but also penetrate into the interior of porous calcium silicate, and a nickel shell layer is uniformly plated on the surface of calcium silicate. This successfully prepared an electromagnetic shielding powder. Compared with the original calcium silicate filler, it not only significantly improves the added value of calcium silicate but also endows it with electrical conductivity, magnetic permeability, and electromagnetic shielding functions. It is not prone to aging, has stable performance, long service life, and low cost, effectively expanding the application scenarios of calcium silicate in the field of functional materials.
[0030] 2) This preparation method also expands the range of substrates that can be selected for chemical plating technology, making calcium silicate a substrate material as well. The substrate material is low in cost, the preparation process is carried out at a low temperature, saving energy, the preparation method is simple and convenient, easy to operate and control, and can be used with conventional equipment. It can be widely used in the chemical nickel plating process of non-metallic powders, is easy to scale up, and is easy to promote and apply.
[0031] 3) Introducing the aforementioned calcium silicate electromagnetic shielding powder into the composite paper system significantly improves the electromagnetic shielding effectiveness of the composite paper, achieving a comprehensive enhancement of mechanical properties, electromagnetic shielding effectiveness, and adaptability to special environments. The resulting composite paper combines the advantages of being lightweight, flexible, and having high shielding performance, and can be widely used in flexible electronics, aerospace, smart wearable devices, and other fields. Attached Figure Description
[0032] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0033] Figure 1 The image shows the XRD pattern of the calcium silicate electromagnetic shielding powder of Example 3 of this invention. Figure 2 The hysteresis loop of the calcium silicate electromagnetic shielding powder in Example 3 of this invention; Figure 3 The conductivity of the calcium silicate electromagnetic shielding composite paper in different embodiments of the present invention; Figure 4 The electromagnetic shielding performance of calcium silicate electromagnetic shielding composite paper in different embodiments of the present invention is shown. Detailed Implementation
[0034] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are also within the scope of protection of the present invention.
[0035] The following examples use conventional instruments and equipment in the art. Unless otherwise specified, the experimental materials and reagents used in the following examples are commercially available and conform to conventional specifications in the art. Any techniques or conditions not specifically described in the following examples can be performed according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0036] It should be noted that, in this invention and the following embodiments, unless otherwise specified, concentration, ratio, etc. are all weight concentration, weight ratio, etc., "%" all represent weight percentage, and "parts" all represent weight parts. These are common writing habits used by those skilled in the art, and therefore will not be repeated in this invention.
[0037] As a preferred embodiment, the preparation method of calcium silicate electromagnetic shielding powder of the present invention includes the following specific steps: S1: Using calcium silicate powder as raw material, an acid etching treatment is performed on the powder for 10-60 minutes at a temperature of 30-60℃ and a solid-liquid ratio of 1g:(50-100)mL using a hydrochloric acid solution with a molar concentration of 0.3-0.6mol / L, followed by filtration to obtain the solid. The calcium silicate powder is porous and honeycomb-like, with an average particle size of 11-13μm. Preferably, the calcium silicate powder is fly ash-based calcium silicate.
[0038] S2: The calcium silicate obtained by acid etching in S1 was sensitized with SnCl2 solution with a concentration of 10-15 g / L at a temperature of 30-60℃ and a solid-liquid ratio of 1 g:(50-100) mL for 10-60 min, and then the solid was filtered off.
[0039] S3: The sensitized calcium silicate obtained in S2 is placed in an activation solution and activated for 10-40 minutes at a temperature of 30-60℃ and a solid-liquid ratio of 1g:(50-100)mL. After washing, it is placed in a reducing agent solution and reduced for 10-30 minutes at a temperature of 30-60℃ and a solid-liquid ratio of 1g:(50-100)mL. After washing, the solid is collected by filtration. The activation solution is silver nitrate solution with a concentration of 10-13g / L; the reducing agent is sodium borohydride solution with a concentration of 40-50g / L.
[0040] S4: Place the calcium silicate obtained in S3 in a chemical plating solution and perform chemical nickel plating treatment for 110-150 min at a temperature of 82-87℃ and a solid-liquid ratio of 1g:(50-100)mL to obtain a nickel-plated calcium silicate suspension. Filter and wash the suspension, and dry it at a temperature of 80-100℃ to obtain calcium silicate electromagnetic shielding powder.
[0041] The composition of the above-mentioned chemical plating solution includes: 33-36 g / L of C6H5Na3O7·2H2O, 25-30 g / L of NiSO4·6H2O, 15-18 g / L of NaH2PO2·H2O, 3-5 g / L of DMAB (dimethylamine borane), 0.01-0.02 g / L of SDS (sodium dodecyl sulfate) and water, with a pH of 10 (which can be adjusted with ammonia, NaOH, etc.).
[0042] As a preferred embodiment, the preparation method of the chemical plating solution is preferably as follows: first, sodium citrate is dissolved in water to prepare a solution, thereby obtaining a sodium citrate solution; then, nickel sulfate, sodium hypophosphite, DMAB and SDS are added sequentially and mixed, and then ammonia is added to adjust the pH to obtain the chemical plating solution.
[0043] As a preferred embodiment, the preparation method of calcium silicate electromagnetic shielding composite paper of the present invention includes the following specific steps: S1: Weigh plant fiber and carbon fiber according to the absolute dry mass ratio, mix them, and then loosen and fully disperse them. Then add the above-mentioned calcium silicate electromagnetic shielding powder and disperse it evenly to prepare a composite suspension with a total solid content of 0.3-0.7%.
[0044] The plant fiber is a mixture of sulfate-bleached softwood pulp and hardwood pulp, with a freeness of 40-50°SR. The mass percentage of the softwood pulp is 70-90%, and the mass percentage of the hardwood pulp is 10-30%.
[0045] The length of the carbon fiber is 5-8mm; the carbon fiber accounts for 15-18% of the paper's basis weight.
[0046] The amount of calcium silicate electromagnetic shielding powder added is 20-60% of the paper's basis weight.
[0047] S2: The above composite suspension is fed into a molding machine, and vacuum-assisted filtration is performed using a 300-1000 mesh screen under a negative pressure of 0.01-0.10 MPa for 1-10 minutes. Then, it is pressed at a pressure of 0.4-0.6 MPa for 4-10 minutes, and dried at a temperature of 105-120℃ for 5-15 minutes to obtain a product with a quantitative content of 60-120 g / m³. 2 Calcium silicate electromagnetic shielding composite paper.
[0048] It should be noted that in this invention, distilled water and / or deionized water are used for both cleaning and washing operations. This invention does not have a special limit on the number of cleaning / washing operations, but it is preferable that the supernatant of the cleaned sample is neutral.
[0049] The present invention will be further described in detail below with reference to embodiments. However, it should be understood that the embodiments are for illustrative purposes only and are not intended to limit the scope of the present invention.
[0050] Example 1:
[0051] A method for preparing calcium silicate electromagnetic shielding powder includes the following specific steps: S1: Using calcium silicate powder as raw material, a 0.3 mol / L hydrochloric acid solution is used to acid-etch the powder for 10 minutes at 30°C and a solid-liquid ratio of 1 g:50 mL. The solid is then filtered. The calcium silicate powder is porous and honeycomb-like, with an average particle size of 12.14 μm. Preferably, the calcium silicate powder is fly ash-based calcium silicate.
[0052] S2: The calcium silicate obtained from acid etching in S1 was sensitized with a SnCl2 solution of 12 g / L at 30 °C and a solid-liquid ratio of 1 g: 50 mL for 10 min, and then the solid was filtered off.
[0053] S3: The sensitized calcium silicate obtained in S2 was placed in an activation solution and activated for 10 min at 30℃ and a solid-liquid ratio of 1 g:50 mL. After washing, it was placed in a reducing agent solution and reduced for 10 min at 30℃ and a solid-liquid ratio of 1 g:50 mL. After washing, the solid was collected by filtration. The activation solution was silver nitrate solution with a concentration of 11 g / L; the reducing agent was sodium borohydride solution with a concentration of 45 g / L.
[0054] S4: The calcium silicate obtained in S3 was placed in a chemical plating solution and subjected to chemical nickel plating for 110 minutes at a temperature of 82℃ and a solid-liquid ratio of 1g:50mL to obtain a nickel-plated calcium silicate suspension. After filtration, washing, and drying at 80℃, calcium silicate electromagnetic shielding powder was obtained.
[0055] The composition of the above chemical plating solution includes: 33 g / L C6H5Na3O7·2H2O, 25 g / L NiSO4·6H2O, 15 g / L NaH2PO2·H2O, 3 g / L DMAB, 0.01 g / L SDS and water, with a pH of 10.
[0056] Example 2:
[0057] A method for preparing calcium silicate electromagnetic shielding powder includes the following specific steps: S1: Using calcium silicate powder as raw material, a 0.6 mol / L hydrochloric acid solution is used to acid-etch the powder for 60 minutes at 60°C and a solid-liquid ratio of 1 g:100 mL. The solid is then filtered. The calcium silicate powder is porous and honeycomb-like, with an average particle size of 12.73 μm. Preferably, the calcium silicate powder is fly ash-based calcium silicate.
[0058] S2: The calcium silicate obtained from acid etching in S1 was sensitized with a SnCl2 solution with a concentration of 15 g / L at a temperature of 60℃ and a solid-liquid ratio of 1 g:100 mL for 60 min, and then the solid was filtered off.
[0059] S3: The sensitized calcium silicate obtained in S2 was placed in an activation solution and activated for 40 min at 60℃ and a solid-liquid ratio of 1 g:100 mL. After washing, it was placed in a reducing agent solution and reduced for 30 min at 60℃ and a solid-liquid ratio of 1 g:100 mL. After washing, the solid was filtered. The activation solution was silver nitrate solution with a concentration of 13 g / L; the reducing agent was sodium borohydride solution with a concentration of 50 g / L.
[0060] S4: The calcium silicate obtained in S3 is placed in a chemical plating solution and subjected to chemical nickel plating for 150 minutes at a temperature of 87℃ and a solid-liquid ratio of 1g:100mL to obtain a nickel-plated calcium silicate suspension. After filtration, washing, and drying at 100℃, calcium silicate electromagnetic shielding powder is obtained.
[0061] The composition of the above chemical plating solution includes: 36 g / L of C6H5Na3O7·2H2O, 30 g / L of NiSO4·6H2O, 18 g / L of NaH2PO2·H2O, 5 g / L of DMAB, 0.02 g / L of SDS and water, with a pH of 10.
[0062] Example 3:
[0063] A method for preparing calcium silicate electromagnetic shielding powder includes the following specific steps: S1: Using calcium silicate powder as raw material, a 0.4 mol / L hydrochloric acid solution is used to acid-etch the powder for 30 minutes at 45°C and a solid-liquid ratio of 1 g:80 mL. The solid is then filtered. The calcium silicate powder is porous and honeycomb-like, with an average particle size of 11.31 μm. Preferably, the calcium silicate powder is fly ash-based calcium silicate.
[0064] S2: The calcium silicate obtained by acid etching in S1 was sensitized by SnCl2 solution with a concentration of 10 g / L at a temperature of 40℃ and a solid-liquid ratio of 1 g:70 mL for 30 min, and then the solid was filtered off.
[0065] S3: The sensitized calcium silicate obtained in S2 was placed in an activation solution and activated for 30 min at 40℃ and a solid-liquid ratio of 1 g:70 mL. After washing, it was placed in a reducing agent solution and reduced for 20 min at 50℃ and a solid-liquid ratio of 1 g:80 mL. After washing, the solid was collected by filtration. The activation solution was silver nitrate solution with a concentration of 10 g / L; the reducing agent was sodium borohydride solution with a concentration of 40 g / L.
[0066] S4: The calcium silicate obtained in S3 is placed in a chemical plating solution and subjected to chemical nickel plating for 120 minutes at a temperature of 85℃ and a solid-liquid ratio of 1g:80mL to obtain a nickel-plated calcium silicate suspension. After filtration, washing, and drying at 100℃, calcium silicate electromagnetic shielding powder is obtained.
[0067] The composition of the above chemical plating solution includes: 34 g / L C6H5Na3O7·2H2O, 27 g / L NiSO4·6H2O, 15 g / L NaH2PO2·H2O, 3 g / L DMAB, 0.01 g / L SDS and water, with a pH of 10.
[0068] Example 4:
[0069] A method for preparing calcium silicate electromagnetic shielding composite paper includes the following specific steps: S1: Plant fibers and carbon fibers were weighed and mixed according to the oven-dry mass ratio, then dispersed thoroughly. The calcium silicate electromagnetic shielding powder from Example 1 was then added and uniformly dispersed to prepare a composite suspension with a total solids content of 0.3%. The plant fibers were a mixture of sulfate-bleached softwood pulp and hardwood pulp, with a freeness of 40°SR. The softwood pulp comprised 70% of the total pulp, and the hardwood pulp comprised 30%. The carbon fibers were 5 mm in length and accounted for 16% of the paper's basis weight. The calcium silicate electromagnetic shielding powder was added at 25% of the paper's basis weight.
[0070] S2: The above composite suspension is fed into a molding machine, and vacuum-assisted filtration is performed using a 300-mesh screen under a negative pressure of 0.01 MPa for 10 minutes. The suspension is then pressed for 10 minutes at a pressure of 0.4 MPa and dried at 105℃ for 15 minutes to obtain a product with a quantitative content of 65 g / m³. 2 Calcium silicate electromagnetic shielding composite paper.
[0071] Example 5:
[0072] A method for preparing calcium silicate electromagnetic shielding composite paper includes the following specific steps: S1: Plant fibers and carbon fibers were weighed and mixed according to the oven-dry mass ratio, then loosened and fully dispersed. The calcium silicate electromagnetic shielding powder from Example 2 was then added and uniformly dispersed to prepare a composite suspension with a total solids content of 0.7%. The plant fibers were a mixture of sulfate-bleached softwood pulp and hardwood pulp, with a freeness of 50°SR. The softwood pulp comprised 90% of the total mass, and the hardwood pulp comprised 10%. The carbon fibers were 8 mm in length and accounted for 18% of the paper's basis weight. The amount of calcium silicate electromagnetic shielding powder added was 45% of the paper's basis weight.
[0073] S2: The above composite suspension is fed into a molding machine, and 800-mesh wire is used for vacuum-assisted filtration under a negative pressure of 0.10 MPa for 1 minute. Then, it is pressed for 4 minutes at a pressure of 0.6 MPa and dried for 5 minutes at 120℃ to obtain a product with a quantitative content of 80 g / m³. 2 Calcium silicate electromagnetic shielding composite paper.
[0074] Example 6:
[0075] A method for preparing calcium silicate electromagnetic shielding composite paper includes the following specific steps: S1: Plant fibers and carbon fibers were weighed and mixed according to the oven-dry mass ratio, then dispersed thoroughly. The calcium silicate electromagnetic shielding powder from Example 3 was then added and uniformly dispersed to prepare a composite suspension with a total solids content of 0.5%. The plant fibers were a mixture of sulfate-bleached softwood pulp and hardwood pulp, with a freeness of 45°SR. The softwood pulp comprised 80% of the total pulp, and the hardwood pulp comprised 20%. The carbon fibers were 6 mm in length and accounted for 15% of the paper's basis weight. The calcium silicate electromagnetic shielding powder was added at 20% of the paper's basis weight.
[0076] S2: The above composite suspension is fed into a molding machine, and 1000-mesh wire is used for vacuum-assisted filtration under a negative pressure of 0.05 MPa for 5 minutes. Then, it is pressed under a pressure of 0.4 MPa for 5 minutes and dried at 105℃ for 10 minutes to obtain a product with a quantitative content of 60 g / m³. 2 Calcium silicate electromagnetic shielding composite paper.
[0077] Example 7:
[0078] A method for preparing calcium silicate electromagnetic shielding composite paper includes the following specific steps: S1: The amount of calcium silicate electromagnetic shielding powder added is 30% of the paper's basis weight. The rest of the preparation process and experimental parameters are the same as in S1 of Example 6.
[0079] S2: Same as S2 in Example 6, yielding a quantitative amount of 60 g / m 2 Calcium silicate electromagnetic shielding composite paper.
[0080] Example 8:
[0081] A method for preparing calcium silicate electromagnetic shielding composite paper includes the following specific steps: S1: The amount of calcium silicate electromagnetic shielding powder added is 40% of the paper's basis weight. The remaining preparation process and experimental parameters are the same as in S1 of Example 6.
[0082] S2: Same as S2 in Example 6, yielding a quantitative amount of 60 g / m 2 Calcium silicate electromagnetic shielding composite paper.
[0083] Example 9:
[0084] A method for preparing calcium silicate electromagnetic shielding composite paper includes the following specific steps: S1: The amount of calcium silicate electromagnetic shielding powder added is 50% of the paper's basis weight. The remaining preparation process and experimental parameters are the same as in S1 of Example 6.
[0085] S2: Same as S2 in Example 6, yielding a quantitative amount of 60 g / m 2 Calcium silicate electromagnetic shielding composite paper.
[0086] Example 10: A method for preparing calcium silicate electromagnetic shielding composite paper includes the following specific steps: S1: The amount of calcium silicate electromagnetic shielding powder added is 60% of the paper's basis weight. The remaining preparation process and experimental parameters are the same as in S1 of Example 6.
[0087] S2: Same as S2 in Example 6, yielding a quantitative amount of 60 g / m 2Calcium silicate electromagnetic shielding composite paper.
[0088] Comparative Example 1: A method for preparing calcium silicate electromagnetic shielding composite paper includes the following specific steps: S1: The amount of calcium silicate electromagnetic shielding powder added is 0% of the paper's basis weight. The rest of the preparation process and experimental parameters are the same as in S1 of Example 6.
[0089] S2: Same as S2 in Example 6, yielding a quantitative amount of 60 g / m 2 Calcium silicate electromagnetic shielding composite paper.
[0090] Experimental Example 1: Performance testing of calcium silicate electromagnetic shielding powder: 1) The crystal structure of the calcium silicate electromagnetic shielding powder in Example 3 was analyzed using X-ray diffraction, and the results are as follows: Figure 1 As shown.
[0091] Depend on Figure 1 It can be seen that the original fly ash-based calcium silicate (FACS) has a distinct characteristic diffraction peak at 2θ = 29.5°, but its peak intensity is relatively weak. After acid etching, the intensity of the characteristic diffraction peak of Acid-FACS is significantly enhanced, and characteristic peaks are also shown at 32.1°, 43.2°, and 49.8°. This is because acid etching removes amorphous impurities and some defects from the surface of FACS, making the calcium silicate crystal structure more regular and improving its crystallinity. However, after electroless nickel plating, the calcium silicate electromagnetic shielding powder, i.e., FACS-Ni particles, shows new characteristic diffraction peaks at 44.5° and 76.6°, corresponding to the elemental Ni (111) and Ni (220) crystal planes, respectively, indicating that Ni is significantly stronger during the electroless nickel plating process. 2+ The nickel was successfully reduced to elemental Ni and coated on the surface of the FACS particles. Meanwhile, due to the blocking effect of the surface nickel shell on X-rays, the characteristic peaks of calcium silicate were not clearly visible in the spectrum, further confirming that the nickel shell layer was successfully applied to the surface of the FACS particles.
[0092] 2) The magnetic properties of the calcium silicate electromagnetic shielding powder in Example 3 were characterized using a vibrating sample magnetometer, and the results are as follows: Figure 2 As shown.
[0093] Figure 2The magnetic properties of calcium silicate electromagnetic shielding powder were demonstrated. As shown in the figure, after 120 minutes of nickel plating, the FACS-Ni particles exhibited a typical S-shaped hysteresis loop and significant soft magnetic properties, with a saturation magnetization reaching 17.18 emu / g. Notably, the hysteresis loop showed no significant remanence or coercivity, indicating that the FACS-Ni particles exhibited superparamagnetism. This unique superparamagnetism allows it to be easily driven by a magnetic field and respond quickly, contributing to improved microwave absorption capabilities and making it a suitable filler for electromagnetic shielding in the preparation of composite paper.
[0094] Experimental Example 2: Performance testing of calcium silicate electromagnetic shielding composite paper: 1) The conductivity of the calcium silicate electromagnetic shielding composite paper prepared in Examples 6-10 and Comparative Example 1 was tested using a four-probe tester. Five parallel tests were performed at different locations for each sample. The average value of the five test data sets was taken as the final conductivity of the sample. The results are as follows: Figure 3 As shown.
[0095] Figure 3 The conductivity of calcium silicate electromagnetic shielding composite paper was demonstrated. When the addition amount of FACS-Ni in Comparative Example 1 was 0 wt%, the conductivity of the composite paper was 0.09 S / cm. With increasing FACS-Ni particle content, the internal conductive network gradually became complete, and the conductivity of the composite paper increased sharply. When the FACS-Ni particle content was 60 wt%, the conductivity reached 11.76 S / cm. These results indicate that calcium silicate electromagnetic shielding composite paper shows promise as an electromagnetic shielding material.
[0096] 2) A vector network analyzer was used to obtain the S-parameters (S11 and S21) of the composite paper in the X-band (8.2-12.4 GHz) frequency range using the waveguide method. Based on the S-parameters, the reflection coefficient (R), transmission coefficient (T), absorption coefficient (A), electromagnetic shielding effectiveness (SET), microwave reflection loss (SER), and microwave absorption loss (SEA) were further calculated and analyzed using corresponding formulas to evaluate its electromagnetic interference shielding performance. The results are as follows: Figure 4 As shown.
[0097] Figure 4The results visually reflect the changes in the total electromagnetic shielding effectiveness (SET), electromagnetic absorption loss (SEA), and electromagnetic reflection loss (SER) of the calcium silicate electromagnetic shielding composite paper. It can be observed that with the gradual increase of the amount of FACS-Ni particles added to the system, the SET and SEA of the composite paper significantly improve, while the SER only shows a slight, gradual increase. Further comparison of the loss proportions reveals that SEA contributes significantly more to the overall SET than SER. This result fully confirms that the calcium silicate electromagnetic shielding composite paper possesses excellent absorption loss advantages for incident electromagnetic waves.
[0098] It should be noted that some detailed steps of the operation are not described in this invention, but are prior art known to those skilled in the art, and therefore will not be repeated here. Furthermore, in this invention, all features defined in the form of numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible secondary ranges and individual numerical values (including integers and fractions) within those ranges.
[0099] It should be noted that the detailed structure of some devices is not described in this invention, but is prior art known to those skilled in the art, and therefore will not be elaborated here. In this invention, structures and devices not specifically limited can be purchased commercially, and those skilled in the art only need to install and operate them according to the accompanying instruction manual, without requiring any creative effort from those skilled in the art.
[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. In this invention, not all possible combinations of the various technical features in each embodiment or implementation are described. As long as the combinations of these technical features do not contradict each other, the various technical features in each embodiment or implementation can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing calcium silicate electromagnetic shielding powder, characterized in that, include: S1: Using calcium silicate powder as raw material, acid etching is performed on it with hydrochloric acid solution, and then the solid is filtered out. S2: After sensitizing the calcium silicate obtained by acid etching in S1 with SnCl2 solution, the solid was filtered off. S3: The sensitized calcium silicate obtained in S2 is placed in an activation solution for activation treatment, washed, then placed in a reducing agent solution for reduction treatment, washed, and filtered to obtain the solid. S4: The calcium silicate obtained in S3 is placed in a chemical plating solution for chemical nickel plating to obtain a nickel-plated calcium silicate suspension. After filtration, washing, and drying, calcium silicate electromagnetic shielding powder is obtained.
2. The method for preparing calcium silicate electromagnetic shielding powder according to claim 1, characterized in that, In S1, the calcium silicate powder is porous and honeycomb-shaped, with an average particle size of 11-13 μm.
3. The method for preparing calcium silicate electromagnetic shielding powder according to claim 1, characterized in that, In S1, the concentration of the hydrochloric acid solution used is 0.3-0.6 mol / L; in S2, the concentration of the SnCl2 solution is 10-15 g / L.
4. The method for preparing calcium silicate electromagnetic shielding powder according to claim 1, characterized in that, In step S3, the activating solution is a silver nitrate solution with a concentration of 10-13 g / L; the reducing agent is a sodium borohydride solution with a concentration of 40-50 g / L.
5. The method for preparing calcium silicate electromagnetic shielding powder according to any one of claims 1-4, characterized in that, In step S4, the chemical plating solution comprises: 33-36 g / L of C6H5Na3O7·2H2O, 25-30 g / L of NiSO4·6H2O, 15-18 g / L of NaH2PO2·H2O, 3-5 g / L of DMAB, 0.01-0.02 g / L of SDS and water, with a pH of 10.
6. A calcium silicate electromagnetic shielding powder, prepared by the method for preparing calcium silicate electromagnetic shielding powder according to any one of claims 1-5, characterized in that, The saturation magnetization of the calcium silicate electromagnetic shielding powder is not less than 15 emu / g.
7. The application of calcium silicate electromagnetic shielding powder in electromagnetic shielding materials, characterized in that, The calcium silicate electromagnetic shielding powder is prepared by the method described in any one of claims 1-5.
8. A method for preparing calcium silicate electromagnetic shielding composite paper, comprising: S1: Weigh plant fiber and carbon fiber according to the absolute dry mass ratio, mix them, and then loosen and disperse them fully. Then add the calcium silicate electromagnetic shielding powder described in claim 6 and disperse it evenly to prepare a composite suspension with a total solid content of 0.3-0.7%. S2: The composite suspension is fed into a molding machine and shaped by vacuum-assisted filtration. After pressing and drying, a product with a quantitative content of 60-120 g / m³ is obtained. 2 Calcium silicate electromagnetic shielding composite paper.
9. The method for preparing calcium silicate electromagnetic shielding composite paper according to claim 8, characterized in that, In S1, the plant fiber is a mixture of sulfate-bleached softwood pulp and hardwood pulp with a freeness of 40-50°SR. The mass percentage of softwood pulp is 70-90%, and the mass percentage of hardwood pulp is 10-30%. The carbon fiber has a length of 5-8 mm and accounts for 15-18% of the paper's basis weight. The amount of calcium silicate electromagnetic shielding powder added is 20-60% of the paper's basis weight.
10. A calcium silicate electromagnetic shielding composite paper, prepared by the method for preparing calcium silicate electromagnetic shielding composite paper according to claim 8 or 9.